Planning the oral health workforce: Time for innovation. Issue 1 (15th December 2020) - Birch, Stephen; Ahern, Susan; Brocklehurst, Paul; Chikte, Usuf; Gallagher, Jennifer; Listl, Stefan; Lalloo, Ratilal; O'Malley, Lucy; Rigby, Janet; Tickle, Martin; Tomblin Murphy, Gail; Woods, Noel
Abstract: The levels and types of oral health problems occurring in populations change over time, while advances in technology change the way oral health problems are addressed and the ways care is delivered. These rapid changes have major implications for the size and mix of the oral health workforce, yet the methods used to plan the oral health workforce have remained rigid and isolated from planning of oral healthcare services and healthcare expenditures. In this paper, we argue that the innovation culture that has driven major developments in content and delivery of oral health care must also be applied to planning the oral health workforce if we are to develop 'fit for purpose' healthcare systems that meet the needs of populations in the 21st century. An innovative framework for workforce planning is presented focussed on responding to changes in population needs, service developments for meeting those needs and optimal models of care delivery.